Antibacterial Therapy: Metal–Organic‐Framework‐Assisted In Vivo Bacterial Metabolic Labeling and Precise Antibacterial Therapy (Adv. Mater. 18/2018). Issue 18 (2nd May 2018) - Mao, Duo; Hu, Fang; Kenry,; Ji, Shenglu; Wu, Wenbo; Ding, Dan; Kong, Deling; Liu, Bin
Abstract : In article number1706831, Deling Kong, Bin Liu, and co‐workers report a new in vivo antibacterial strategy. With the help of a metal–organic framework, a functionalized amino acid, and photosensitizer nanoparticles with aggregation‐induced emission, bacteria hidden in the body can be specifically detected and killed via bioorthogonal reaction, followed by imaging‐guided photodynamic therapy. This in vivo metabolic labeling method may emerge as a promising alternative to antibiotics in antibacterial therapy.